2019
DOI: 10.1149/09101.1751ecst
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of the A-Site Deficient Perovskite La0.65Sr0.3Cr0.85Ni0.15O3-δ as Fuel Electrode for High Temperature Co-Electrolysis Enhanced by In Situ Exsolution of Ni Nanoparticles

Abstract: Lanthanum strontium chromite (LSC) perovskite partially doped with 15% of Ni on the B-site as reducible transition metal was investigated with the aim to perform in situ exsolution under reducing conditions. A-site deficient compounds were formulated to enhance the exsolution of the electrocatalyst. Single phase is achieved with the formulation La0.65Sr0.3Cr0.85Ni0.15O3-δ (L65SCN) and has been characterized by X-ray diffraction (XRD), Rietveld refinement and scanning electron microscopy (SEM). Exsolution was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 8 publications
0
9
1
Order By: Relevance
“…The main phase is identified as an LSCrN perovskite structure, consistent with the ones observed in our previous study (PDF# 01-076-7024). [16] Furthermore, both powders show a secondary SrCrO 4 phase that cannot be detected anymore after reduction. This is consistent with literature studies that reported the formation of SrCrO 4 after the annealing of chromites at high temperature in air.…”
Section: Crystallographic Structure Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…The main phase is identified as an LSCrN perovskite structure, consistent with the ones observed in our previous study (PDF# 01-076-7024). [16] Furthermore, both powders show a secondary SrCrO 4 phase that cannot be detected anymore after reduction. This is consistent with literature studies that reported the formation of SrCrO 4 after the annealing of chromites at high temperature in air.…”
Section: Crystallographic Structure Analysismentioning
confidence: 96%
“…Recently, we have introduced the chromite formulation La 0.65 Sr 0.3 Cr 0.85 Ni 0.15 O 3-δ (L65SCrN) and demonstrated the successful up-scaling of exsolution-based perovskite electrodes from the commonly used button cell level to 5 × 5 cm 2 large ESC. [16] The performance of the cell in (co-)electrolysis mode was promising. In the present study, cells with this perovskite electrode are investigated in fuel cell operation.…”
Section: Introductionmentioning
confidence: 99%
“…Next, these solutions were stirred and heated on a hot plate until a dark green-colored gel was formed. Previous thermogravimetric measurements in synthetic air performed on these gels indicated that the solvent evaporation takes place at $91 C followed by an exothermic self-combustion reaction at $220 C. 24 Therefore, in this study, the gels were heated up to $220 C where self-combustion occurred. Finally, the resulting ceramic precursors were calcined in air at a rate of 3 C min À1 up to 1400 C for one hour since it was the minimal ring temperature at which a perovskite phase could be achieved, 24 which is consistent with previous studies on lanthanum chromites.…”
Section: Introductionmentioning
confidence: 92%
“…The electrochemical performance of the L65SCrN fuel electrode in the ESC architecture was studied on the test bench described elsewhere. 24 The fuel electrode was contacted with a platinum mesh and the oxygen electrode with a gold mesh. A gold frame was used as a sealant between the fuel and the air side.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…The change from a fossil fuel-based to a renewable energy-based system requires the development of resource efficient materials with a long lifetime for energy conversion technologies. In this regard, mixed ionic-electronic conducting (MIEC) oxygen transport materials have drawn increasing interest due to their high potential for various energy conversion applications such as the oxygen transport membrane (OTM) for producing oxygen from air [1][2][3][4][5][6][7][8][9][10][11][12], electrolytes for batteries [13][14][15], cathode materials for solid oxide fuel cells [16][17][18], catalysts [19][20][21], and in membrane reactors [21][22][23]. With the current background of increases in CO 2 emissions and fossil resources depletion, CO 2 capture and utilization have been intensively researched to reduce CO 2 emissions, including thermolysis, membranes have received less attention in the literature for the oxygen transport process.…”
Section: Introductionmentioning
confidence: 99%